The magnetic storms of 3–4 August 2010 and 5–6 August 2011: 1. Ground‐ and space‐based observations. Issue 3 (7th March 2017) - Valladares, C. E.; Eccles, J. V.; Basu, Su.; Schunk, R. W.; Sheehan, R.; Pradipta, R.; Ruohoniemi, J. M.
Abstract: We have used total electron content (TEC) values from low, middle, and high latitudes recorded over the American continent and density and ion temperature measured in situ by the DMSP‐F15 and F17 satellites during the geomagnetic storms of 3–4 August 2010 and 5–6 August 2011 to study the formation and dynamics of plasma density enhancements that developed during these two storms. Common to both storms are the timing of the main phase that extends between 20 and 24 UT and their seasonality with both storms occurring near the end of the Northern Hemisphere summer solstice. During both storms, TEC data show incipient equatorial anomalies lacking a poleward expansion beyond 20° magnetic latitude. Two large‐scale TEC enhancements were observed at middle latitudes showing a complicated pattern of structuring and merging. The first TEC enhancement corresponds to a storm‐enhanced density (SED) seen between 21 and 01 UT on the following day. The second TEC enhancement was observed over Central America, located equatorward of the SED and apparently moving northward. However, careful analysis of the TEC values indicates that this second TEC enhancement is not transported from lower latitudes through a superfountain effect. Instead, the enhanced plasma has a local origin and is driven by a southward directed meridional wind that moves plasma up the tilted magnetic field lines. DMSP flights passing over the second TEC enhancement show a reduction of the ion temperature, confirming an adiabatic expansion of the plasma as it moves up the field lines. It is concluded that the midlatitude TEC enhancements do not arise from a low‐latitude ionospheric fountain effect. Key Points: Regional maps of TEC showing the existence of two regions of enhanced densities during two magnetic storms During the storms, the equatorial anomaly is weakly developed and does not contribute to the SED Neutral winds have an important role on producing TEC enhancements at midlatitudes during magnetic storms